THE DYNAMIC LOADING IN LONGITUDINAL AND TRANSVERSE REINFORCEMENT AT INSTANT EMERGENCE OF THE SPATIAL СRACK IN REINFORCED CONCRETE ELEMENT UNDER THE ACTION OF A TORSION WITH BENDING - Demyanov, Aleksey; Kolchunov, Vladimir Ivanovich (Journal of Applied Engineering Science, 2017)
It is proposed the computational model of the dynamic loading in longitudinal and transverse reinforcement at instant emergence of the spatial сrack in reinforced concrete constructions under the action of torsion with bending. The dependences have been obtained for the determination of stresses in stretched reinforcement, vertical and horizontal reinforcement stirrups in cross section with a crack.